Konsep Kebebasan Menurut Jean-Jacques Rousseau dan Relevansinya Bagi Demokrasi Indonesia Saat Ini (Sebuah Kajian Filosofis - Kritis) - Romanus Piter; Valentinus . (Forum, 2021)
The focus of this paper is a discussion of the concept of freedom according to Jean-Jacques Rousseau, one of the philosophers of the Enlightenment. Rousseau's concept of freedom is always interesting to discuss in the context of a country that applies democracy as its political system, one of which is Indonesia. In discussing the concept of Rousseau's freedom, it is relevant to Indonesia's current democracy, which is in a state of flawed democracy according to the research results of The Economist Intelligence Unit in 2020. The goal to be achieved is to find new ideas as a solution to improve the quality of Indonesian democracy for the better. The method used in this paper is a qualitative method in the form of literature review. The findings in this paper is that the quality of freedom in Indonesian democracy is still very low, especially in the fields of religion and education. The task to fight for this freedom is first of all in the hands of the leaders of the nation and state.